Dihalobenzene Shape Sorting by Nonporous Adaptive Crystals of Perbromoethylated Pillararenes. (14th February 2019) - Li, Errui; Zhou, Yujuan; Zhao, Run; Jie, Kecheng; Huang, Feihe
Abstract: The separation of dihalobenzene isomers, such as dichlorobenzene isomers and difluorobenzene isomers, has a high practical value in both synthetic chemistry and industrial production. Herein we provide a simple to operate and energy‐efficient adsorptive separation method using nonporous adaptive crystals of perbromoethylated pillar[5]arene (BrP5 ) and pillar[6]arene (BrP6 ). BrP6 crystals show a preference towards the ortho isomer of dichlorobenzene in isomer mixtures, but cannot discriminate difluorobenzene isomers. Single‐crystal structures reveal that this selectivity is derived from the stability of the new host–guest crystal structure of BrP6 after uptake of the preferred guest and the binding strength of the host–guest interactions. Furthermore, because of the reversible transition between guest‐free and guest‐loaded structures, BrP6 crystals are recyclable. Abstract : Getrennte Wege : Eine einfache und energieeffiziente Trennung von Dihalogenbenzolen wird durch nichtporöse Kristalle von perbrommethyliertem Pillar[6]aren (BrP6 ) ermöglicht. BrP6 ‐Kristalle zeigen eine Präferenz für das ortho ‐Isomer von Dichlorbenzol, können aber nicht zwischen Difluorbenzol‐Isomeren unterscheiden.